Non-Pharmacological Pain Management of Primary Dysmenorrhea Using Pineapple Juice in Adolescent Girls - Nuridha Fauziyah; Fitri Handayani (Citra Delima Scientific journal of Citra Internasional Institute, 2026)
Dysmenorrhea, or menstrual pain, is recognized as the leading factor contributing to repeated absences from school among students. The treatment of menstrual pain is often carried out through pharmacological approaches, particularly the use of analgesic medications, which are widely utilized to reduce pain intensity. However, primary dysmenorrhea can also be managed through non-pharmacological approaches, one of which is pineapple juice, which contains bromelain. This research was conducted to investigate the influence of pineapple juice on the intensity of primary dysmenorrhea among nursing students in the Nursing Study Program at Politeknik Negeri Subang. The study population included all first-year female students experiencing primary dysmenorrhea. 32 participants were selected using a purposive sampling method, and the research applied a pre-experimental one-group pretest–posttest design. Data collection began with the observation of dysmenorrhea pain intensity, followed by the administration of 230 ml of pineapple juice once daily during the occurrence of menstrual pain. The intervention outcomes were monitored for 60 minutes following administration. Data were analyzed using the Wilcoxon test, which produced a Z score of –3.873 and a p-value of 0.000. Since the p-value was lower than the significance threshold (α = 0.05), the findings indicated that pineapple juice had a statistically significant effect in reducing menstrual pain among adolescent girls.